Development of Gold Padding to Gold Investment at PT. Pawnshop Service Unit Muara Bulian Branch - Durotul Kolbiah, Fitri; Durotul, Tsani (Sunan Kalijaga International Journal on Islamic Educational Research, 2024)
The value of gold investment is not eroded by inflation, the price trend continues to increase, buying and selling transactions are flexible, making gold an alternative investment choice. The aim of this research is to determine and describe the development of sharia gold pawning linked between gold pawning and gold investment as protection for assets. The method used in this research is descriptive, this research data was obtained from interviews with pawnshop customers and questionnaires and used secondary data from library literature, other relevant source books. The results of this research show the development of sharia pawnshops from sharia gold pawning, which was originally only an alternative financing and additional capital in the short term, has actually begun to be used as a means for investing, by taking advantage of the increase in the value of gold prices and the convenience and relief of sharia gold pawning. Investing in gold by buying, saving and then selling using pawn services, namely by buying, saving and then pawning is a strategy for investing in gold and a solution for maintaining gold investments